Analisis Kepuasan Pelayanan Kesehatan Di Puskesmas Talaga Bodas - Ida, Ida jalilah; anglyn, Anglyn Gabriel (Jurnal Ekonomi Bisnis Manajemen Prima, 2023)
This research focuses on the satisfaction of healthcare providers as experienced directly by patients. The research method used is a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation of patients/families, as well as the leadership and staff at Talaga Bodas Community Health Center. The study found that the reliability aspect of the services provided at Talaga Bodas Community Health Center is characterized by a high level of discipline and reliability, as perceived by patients. The responsiveness aspect of the services provided at Talaga Bodas Community Health Center is highly responsive to patients, especially in emergency cases or when patients require immediate assistance. The assurance aspect of the services provided at Talaga Bodas Community Health Center is characterized by friendly, polite, and respectful behavior of the staff towards patients, creating a sense of comfort. The empathy aspect of the services provided at Talaga Bodas Community Health Center is demonstrated by healthcare providers showing a high level of empathy and concern. The tangible aspect of the services provided at Talaga Bodas Community Health Center is reflected in the good facilities and infrastructure available. Overall, patients express satisfaction with the services provided at Talaga Bodas Community Health Center.